Medical and social efficiency of clinical examination and recovery treatment of patients after metal-ceramic dental prosthetics - N. A. Martirosian; S. I. Risovanny; A. N. Bondarenko; M. A. Bondarenko; N. Yu. Seferyan (Кубанский научный медицинский вестник, 2015)
According to the survey of 100 patients studied medical and social effectiveness of clinical examination after prosthetics metal-ceramic prosthesis. It is proved that this method of organizing and carrying out medical examination of rehabilitation therapy allows to improve the quality of life of patients 1.4 times.